Prediction of the Number of Passengers at Yogyakarta Airport - Imam Safawi Ahmad; Agus Suharsono; Elly Pusporini (LPPM Institut Teknologi Sepuluh Nopember, 2019)
The development of air transportation services is growing up. Based on the report of Central Bureau of Statistics (BPS) in January-October 2015, the number of passengers reached 67.5 million. This number is increased by 12.8% from the previous year with only 58.9 million. Overall, there was increased in the number of passengers caused overload of capacity. One of international airports in Indonesia is Adisutjipto in Yogyakarta. The airport officer wants to develop in terms of airplane schedule management and the number of aircrafts used to calculate the number of passengers in the future. In this study, we aimed to forecast next period by using three methods, namely ARIMA, Exponential Smoothing and Combination of both univariate models. This research gives results that generally all route significantly increased every year with Denpasar, Jakarta, Pontianak and Singapore as exception. They were declined slightly in 2015. The number of passengers of departure and arrival routes are affected by seasonal impact. In addition, the model for departure and arrival data had similar models. Another result is combination method did not produce better results than the univariate method. The fit model for predicting data passenger is ARIMA seasonal methods.